Cardozo Martínez, C.A.; Mrad de Osorio, A.; Maldonado Gómez, O. & Cely Galindo, G. (Editores). (2009). Ética en investigación. Una responsabilidad social. Bogotá: Universidad Nacional de Colombia & Pontificia Universidad Javeriana. Número de páginas: 288 - Hoyos Vásquez, Guillermo; Pontificia Universidad Javeriana (2009)
null